Analisa Quenching Air Dan Oli Terhadap Terhadap Nilai Kekerasan Permukaan Baja Karbon Rendah Hardfacing Menggunakan Las Smaw Dengan Polaritas DC- Dan DC+ - Hermawati, Lilin; Pratomo, Sunu Arsy; Budiyanto, Lilik (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
When welding, you don't have to connect two metal materials, you can also weld the thickness of the component. Steel is a metal material that can be used in the engineering field to make alloys of other metals so that they can have better material properties than the original metal material. One thing that can be done to increase resistance to wear is to increase the surface hardness of the workpiece. This research carried out an analysis to increase the hardness of the surface of low carbon steel after heat treatment for 60 minutes with variations in quenching media resulting from hardfacing using SMAW welding (shield metal arc welding) with DC+ and DC- polarities. The data analysis technique used in this research is specimen testing. The results obtained later by the research show that DC+ polarity has higher hardness in all specimens tested with a value of 418.66 VHN water quenching, 402.8 VHN oil quenching, 348 VHN non-treatment when compared with DC- polarity with a value of 405, 92 VHN quenching water, 374.02 VHN quenching oil and 323.38 VHN non-treatment. Quenching media with water obtained the highest hardness results with a value of 405.92 VHN.